Process of Privatization: International Initial Public Offering (IPO) of an Indonesian State-Owned Enterprise (SOE) - Mangkusubroto, Kuntoro (SBM ITB, 2011)
This paper describes process of privatization through international initial public offering (IPO) of anÃ‚Â Indonesia State Owned Enterprice (SOE). The case referred to in this paper is PT Tambang Timah, anÃ‚Â Indonesian Mining SOE, which previously suffered from fundamental change in the industry but wasÃ‚Â successfully turned around prior to its IPO. The discussion starts with the background on privatization ofÃ‚Â SOEs Ã‚Â by Ã‚Â highlighting Ã‚Â the Ã‚Â historical Ã‚Â policies Ã‚Â of Government Ã‚Â toward Ã‚Â SOEs, Ã‚Â environmental Ã‚Â changesÃ‚Â leading to improving performance of SOEs, and IPO as an alternative to improving SOE's performance.Ã‚Â It followed by a summary description of a successful turn-around and privatization of PTTambang TimahÃ‚Â as the case example. It concluded with some lessons learned from the process as well as the specificÃ‚Â case.Keywords: Initial public offering, PT Tambang Timah, mining